Comparación de impactos ambientales entre las alternativas de corte - relleno y viaducto, para la construcción de carreteras: revisión de un caso de estudio (2018)
In this article a comparison is made between the results of the evaluation of environmental impacts (EvIA) of two alternatives for road construction, cut-fill and viaduct, based on the analysis of a case study. The evaluation of the first alternative (cut-fill) corresponds to the real EvIA, carried out by the consultant of the studies and designs of the case study analyzed. For the second alternative, a viaduct design was proposed, from which the EvIA was made following the same methodology used by the consultant, which is based on the Conesa - Fernández proposal, using only qualitative results. As a result, it is concluded that each alternative has different advantages and disadvantages from the environmental point of view and the best alternative will depend on the conditions of the affected environment and environmental zoning of each project.